FENOMENA PROSTITUSI ONLINE DI JAKARTA SELATAN - Natasya Dwi Febriana; Kusyogo Cahyo; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
According to the research of Sedyaningsih by 2015 that South Jakarta has the highest HIV/AIDS prevalence caused by online prostitution activities, namely of 372 cases out of 1.032 cases of online prostitution. The purpose of this research is to analyze the phenomenon of online prostitution in South Jakarta area focused on the practice of commercial sex workers behavioral. This research is qualitative research with the descriptive approach. The subjects in this study amounted to 14 people which consists of 5 research subjects and 9 triangulation subjects. The results showed that the whole subject of research is the commercial sex workers that can be booked via the internet and provide services to have sex with their clients, on the normative beliefs variables that most of the research subjects knows the online prostitution from their closer friend, on the attitude variables research subjects shows negativity attitude towards their job, on the motivational variable shows that most of the research subjects wants to be recognized in their social environment and cannot detached from the luxury lifestyle, on the subjective norm variables shows that most of the research subject does not want to be known as commercial sex workers of online prostitution, on the intention variable research subjects shows that the whole research subjects showed positive intention since the very first time they get to know the online prostitution. Data analysis in this study uses qualitative descriptive method. The behavior of commercial sex workers on online prostitution in South Jakarta based on their motives are self-actualization in group social and economic motives. Behavior of online prostitution is considered risky because the commercial sex workers online prostitution do high-risk sexual behavior as well as online prostitution is disguised prostitution so it cannot be observed by the Government. So the further monitoring of activities online prostitution in South Jakarta is very necessary.